Toward a Philosophical Anthropology of Religion: Reconciling a Naturalistic Approach to the Study of Religion with the Belief of the Believer - Rennie, Bryan S. (Archaeus, 2002)
The explicit intention of this article, as asserted by the author himself, is to illustrate the means by which a "fully rational recognition of the irreductibility of the belief of the believer" would be possible. In relation to the main paradigm of the study of religion used in the US, polarized between a naturalistic approach and a theological approach, Rennie tends to avoid "a turn away from the naturalistic History of Religion". In the constitution of his article, Rennie takes into discussion certain conceptual paradigms, characteristic - on the one hand - for the Anglo-American milieu of the study of religion, as reflected in the works of scholars such as: Clifford Geertz, Russell MacCutcheon, Ninian Smart, Nancy Frankenberry, Hans Penner, Burton Mack, on the other hand - for Eliade’s thought, illustrated mainly by the latter’s Myth and Reality (New York, 1963) and The Quest: History and Meaning in Religion (Chicago, 1969).